Analisis Risiko Sosial pada Proyek Perumahan Terjangkau di Jawa Timur - Salsadila Audiary Samudra; Farida Rachmawati (LPPM Institut Pendidikan Nusantara Global, 2026)
Indonesia is currently facing a housing ownership crisis, with a backlog that reached 12.7 million units in 2023. The rapid escalation of urban land prices, which has grown far faster than household income, has significantly reduced housing affordability, especially for low-income communities. As a response, the government has promoted subsidized housing programs; however, their implementation at the local level continues to encounter substantial challenges. Limited availability of urban land often forces projects into peripheral areas, potentially creating inequality in access to public facilities, employment opportunities, and basic urban services. These conditions generate various social risks that may undermine the sustainability of affordable housing developments. This study aims to identify key social risks in affordable housing projects and to determine appropriate mitigation actions across different project phases. The research adopts a literature review approach combined with secondary data analysis, utilizing the Power–Interest Matrix and the Probability–Impact Matrix as analytical tools. The results indicate a dynamic shift in stakeholders who possess high power and high interest at different stages of project development. During the construction phase, four major social risks were identified, whereas in the operational or property management phase, six social risks emerged as top priorities. High-level social risks were found to be a predictable outcome of imbalanced stakeholder power and interest relationships. Overall, the findings emphasize the critical role of Governments, Developers, and Contractors in proactively managing social risks. Preventive and corrective measures must use tailored communication and stakeholder engagement to reduce social risks and improve project success overall outcomes.